Eagle’s syndrome: retromandibular approach as a surgical management - Agarwal, Amit; Das, Amber; Srivastav, Pritika (International Surgery Journal, 2026)
Eagle's syndrome is a pathology characterized by sign and symptoms affecting the pharyngeal and cervical regions, due to enlarged styloid process or calcified stylomandibular or stylohyoid ligaments originating from same. The styloid process is thin, cylindrical and pointed bony structure originating from tympanic part of temporal bone projecting inferiorly and anteriorly at base of skull, which is in close proximity to vital neuro vascular structure of cervical region. The styloid process is considered normal in length in Asian population, when it's dimensions do not exceeds 30 mm. Diagnosis can be made clinically by palpating bony prominence between angle of mandible and mastoid process, and transoral palpation of tip of styloid process. Diagnosis can be confirmed by radiographic investigation, most preferably computed tomography (CT) imaging. Extraoral retromandibular approach of styloidectomy is best and most efficient.